Teacher Management in Encouraging Islamic Education Reform - Putera, Odsisa; Martias, Martias; Zainal, Zainal; Ringgit, Awang (STIT Ahlussunnah Bukittinggi, 2024)
Islamic education systems in many countries still face challenges in terms of quality and relevance to modern society's needs. Islamic teachers are often under-trained in classroom management and developing innovative curricula. This article aims to explore the role of teacher management in promoting Islamic education reform. This study seeks to understand how Islamic teachers can manage classrooms and develop curricula that are more effective and relevant to modern society's needs. This study uses a qualitative method, conducting interviews and observations with Islamic teachers and students in several Islamic schools. Data is analyzed using thematic analysis to identify emerging patterns and themes. The research findings show that effective teacher management can improve the quality of Islamic education. Teachers who are trained in classroom management and developing innovative curricula can increase student motivation and achievement. Additionally, this study finds that Islamic teachers need to have adequate knowledge and skills in managing classrooms and developing curricula that are relevant to modern society's needs. This study has important implications for Islamic education policy and teacher training. Governments and Islamic education institutions need to give greater attention to teacher training and developing innovative curricula. Additionally, this study suggests that Islamic teachers need to have adequate knowledge and skills in managing classrooms and developing curricula that are relevant to modern society's needs. Thus, Islamic education can become more effective and relevant to modern society's needs.